In Situ Mesopore Formation in SiOx Nanoparticles by Chemically Reinforced Heterointerface and Use of Chemical Prelithiation for Highly Reversible Lithium-Ion Battery Anode - Gong, Sanghyuk; Lee, Yeongje; Choi, Jinkwan; Lee, Minah; Chung, Kyung Yoon; Jung, Hun-Gi; Jeong, Sunho; Kim, Hyung-Seok (Wiley - V C H Verlag GmbbH & Co., 2023)
SiOx is a promising next-generation anode material for lithium-ion batteries. However, its commercial adoption faces challenges such as low electrical conductivity, large volume expansion during cycling, and low initial Coulombic efficiency. Herein, to overcome these limitations, an eco-friendly in situ methodology for synthesizing carbon-containing mesoporous SiOx nanoparticles wrapped in another carbon layers is developed. The chemical reactions of vinyl-terminated silanes are designed to be confined inside the cationic surfactant-derived emulsion droplets. The polyvinylpyrrolidone-based chemical functionalization of organically modified SiO2 nanoparticles leads to excellent dispersion stability and allows for intact hybridization with graphene oxide sheets. The formation of a chemically reinforced heterointerface enables the spontaneous generation of mesopores inside the thermally reduced SiOx nanoparticles. The resulting mesoporous SiOx-based nanocomposite anodes exhibit superior cycling stability (approximate to 100% after 500 cycles at 0.5 A g(-1)) and rate capability (554 mAh g(-1) at 2 A g(-1)), elucidating characteristic synergetic effects in mesoporous SiOx-based nanocomposite anodes. The practical commercialization potential with a significant enhancement in initial Coulombic efficiency through a chemical prelithiation reaction is also presented. The full cell employing the prelithiated anode demonstrated more than 2 times higher Coulombic efficiency and discharge capacity compared to the full cell with a pristine anode.